Partial trisomy 17q and partial monosomy 20q in a boy with craniosynostosis. (25th November 2014) - Marques, Felipe; Heredia, Romina; de Oliveira, Claudiner; Cardoso, Maria Terezinha; Mazzeu, Juliana; Pogue, Robert
<x xml:space="preserve">Abstract</x> Craniosynostosis is defined as a premature fusion of at least one cranial suture, which can be accompanied by other findings. Of syndromic cases, 14–22% have been associated with chromosomal rearrangements. This report describes a Brazilian boy with syndromic craniosynostosis who also presented with intellectual disability, microcephaly, frontal bossing, bitemporal narrowing, short neck, syndactyly, and cardiac defects. Chromosome banding showed an apparently normal male karyotype. Subsequent chromosomal microarray analysis (CMA) using the Affymetrix CytoScan 750 K Array showed a duplication of 2.1 Mb on chromosome 17q and a deletion of 1.4 Mb on chromosome 20q. The data suggested an unbalanced translocation, which was confirmed by fluorescence in‐situ hybridization analysis (FISH). While there are several reports in the literature of chromosome 17q duplication syndrome accompanied by partial monosomies of other chromosomes, this is the first case featuring partial monosomy of 20q. The patient́s phenotype is generally consistent with 17q duplication syndrome, however craniosynostosis has rarely been associated with this chromosomal anomaly. © 2014 Wiley Periodicals, Inc.